comparing with Pp+Qq=R, we get
P=x-y
Q=y-x-z
R=z
the corresponding system of equations is
"\\frac{dx}{x-y}=\\frac{dy}{y-x-z}=\\frac{dz}{z}" ......1
adding all the above equations in 1
"\\frac{dx+dy+dz}{0}=\\frac{d(x+y+z)}{0}"
d(x+y+z)=0
x+y+z=f is the first independent integral
now considering 1 again,
"\\frac{dx-dy+dz}{x-y+z}=\\frac{d(x-y+z)}{x-y+z}"
"d[\\frac{(ln (x-y+z))}{z^2}]=0"
g= (x-y+z)/z2 is the second independent integral
the general solution is
U(P,Q)=0 WHERE P= x+y+z and Q=x-y+z/z2 ....2
since we have z=1
P= x+y+1 and Q=x-y+1
so, on solving
x= "\\frac{P+Q}{2}-1 and\n y= \\frac{P-Q}{2}"
Now, given x2=y2=1
putting values of P and Q,
P(P-2)+Q(Q-2)=0
U(P,Q)= P(P-2)+Q(Q-2)
Putting the values of P and Q from 2
(x+y+z)(x+y+z-2) + "\\frac{x-y+z}{z^2}[\\frac{x-y+z}{z^2}-2] =0"
Comments
Leave a comment